Pengaruh Kecerdasan Intelektual, Komitmen Dan Budaya Kerja Terhadap Kinerja Karyawan Badan Kepegawaian Dan Pengembangan Sumber Daya Manusia Kota Probolinggo - Hasan, Miftahul; hendra, Joni; Pujiastuti, Agustina (Universitas Panca Marga, 2024)
The reset was carried out by the Probolinggo City BKPSDM by looking for the impact of emotional intelligence, work discipline and work motivation on the work results of Probolinggo City BKPSDM employees. Quantitative reset by causal associative linkage, the type of reset used. This reset the number of samples used was 43 respondents. The sampling technique is saturated sampling. In proving and analyzing this, so validity and reliability tests, classical assumption tests, R2 determination analysis, linear regression tests and hypothesis tests. Test results: 1) There was an impact of intelligence on the work results of employees in the city of Probolinggo BKPSDM. 2) The work dedicated to the work of Probolinggo City BKPSDM has an impact. 3). Work culture has an impact on the job performance of employees in BKPSDM Probolinggo city.